(untitled) (Research, Society and Development, 2025)
Introduction: Hydatidiform mole pregnancy is a relatively uncommon complication of gestation. However, it carries a potential risk of evolving into forms that require systemic treatment and can be devastating and even lethal. The term hydatidiform mole encompasses two distinct histopathological and clinical entities: partial and complete moles. The differences between these two forms are critical due to the risk of progression to persistent forms. Objective: This study aims to analyze the socio-epidemiological profiles of molar pregnancy cases recorded in Brazil from 1996 to May 2023, contributing to the reduction of maternal mortality by identifying high-risk groups. Methodology: This is an ecological, time-series study with a quantitative approach, based on data from the Mortality Information System (SIM) of DATASUS. Results: Brazil recorded 144 maternal deaths due to hydatidiform mole, with an annual average of 5.14 cases, indicating that it is a rare pathology. A significant peak of deaths (n=11) occurred in 2010, compared to other years and the annual average. The analysis reveals that the majority of women who were victims of hydatidiform mole were aged 20 to 29 (n=59; 40.97%), followed by those aged 30 to 39 (n=31; 21.53%). Predominantly, victims were mixed-race (n=55; 38.19%) and white (n=48; 33.33%) women, single (n=76; 52.78%), and had an unknown education level (n=41; 28.47%), followed by 4 to 7 years of schooling (n=38; 26.39%).